Gamified Mobile Learning Apps and Their Impact on Critical Thinking Skills for Environmental Education in Primary Students - Sain, Zohaib Hassan; Pllana, Duli; Lama, Alma V.; Abdullah, Nurulannisa; Shahzadi Hina, (Journal of Multidisciplinary Research Advancements, 2025)
Gamified mobile learning applications are transforming primary education by actively engaging young learners in developing critical thinking, particularly within environmental education. With the Single National Curriculum (SNC) in Pakistan emphasising both critical thinking and environmental awareness, there is an urgent need for innovative educational tools that can address these competencies from the early grades. This study examines how gamified mobile learning apps themed on environmental science can help Pakistani elementary school students think more critically. A quasi-experimental design was used to assign 120 students to two groups: an experimental group that used gamified environmental education apps and a control group that received regular lessons. Standardised tools were used to assess critical thinking about climate, sustainability, and ecological problem-solving before and after an eight-week intervention. It was found that the critical thinking scores of the experimental group increased from 58.3 to 72.4, whereas those of the control group increased only from 59.1 to 63.9, a 24% decrease. Many teachers and students who were asked said that students who used apps, such as games, were better at handling problems and knew more about environmental issues. The results show that adding gamified digital tools for environmental education to Pakistan's primary school curriculum could significantly help students learn to think critically and understand climate change. To increase the use of gamified mobile learning in early education to help children explore the world and develop 21st-century thinking skills, the paper suggests changes to policies and teacher training.